1903 Or. Laws 309-10 - (:unkn) unknown (My University, 1903)
An Act to Regulate and Prohibit the Sale, Barter, Exchange, or Gift of Explosives, Firearms or Other Articles of a Like Kind, to Children Under the Age of Fourteen Years, and to Punish the Violation of the Provisions of this Act. §§ 1-2: It shall be unlawful to sell, exchange, barter, or give to any child, under the age of fourteen years, any explosive article or substance, other than an ordinary firecracker, containing ten grains of gunpowder; or to sell, exchange, barter, or give to any such child any firearms, or other device of a like kind, ordinarily used or ordinarily capable of being used in discharging gunpowder in a greater quantity than ten grains; and it is herby made unlawful in any event to sell, exchange, barter, or give to any child, under the age of fourteen years, any instrument or apparatus, the chief utility of which consists in the fact that it is used, or is ordinarily capable of being used, as an article or device to increase the force or intensity of such explosive, or to direct or control the discharge of any such explosive
Keywords: TRANSFER - MINORS